A Phase I Study to Evaluate the Safety of the Herbal Medicine SH003 in Patients With Solid Cancer - Chunhoo Cheon KMD, PhD; Seong-Gyu Ko KMD, MPH, PhD (Integrative Cancer Therapies, 2020)
Background: Cancer is a major health problem worldwide and the leading cause of death in many countries. Preclinical studies have shown the therapeutic anticancer effects of SH003, a novel herbal medicine containing Astragalus membranaceus, Angelica gigas , and Trichosanthes kirilowii . The present study investigated the maximum tolerated dose of SH003 in patients with solid cancers. Methods: This open-label, dose-escalation trial used the traditional 3 + 3 dose-escalation design. Patients with solid cancers were recruited and administered 1 to 4 tablets of SH003 thrice daily for 3 weeks according to the dose level. Adverse events were evaluated according to the Common Terminology Criteria for Adverse Events (CTCAE). Dose-limiting toxicities (DLTs) were defined as Grade 3 or higher adverse events based on CTCAE. The maximum tolerated dose was defined as the highest dose at which no more than 1 of 6 patients experienced DLT. Results: The present study enrolled 11 patients. A total of 31 adverse events occurred. According to the CTCAE, all the observed adverse events were grade 2 or less and no adverse events of grade 3 or more corresponding to DLT occurred. Conclusion: The study results indicated that the maximum tolerated dose of SH003 was 4800 mg/day. A Phase 2 study is required to determine the efficacy of SH003 in patients with cancer at a dose of 4800 mg/day or less.